A Feasibility study on rice-mungbean with sesame blend snackfood - Parrilla, Liza J.; Que, Jocelyn R.; Zomil, Joanna V. (Diliman, Quezon City College of Engineering, 1996)
The market today is saturated with products from the snack foods industry. Yet despite the already many local manufacturers who are in the business and the imports we're getting, an in-depth analysis of the market shows that there still exists a large unsatisfied gap between the supply and the demand for these products. Studies also show that while many of the puffs, curls and chips in the market boasts of a variety of flavors - from cheese to sour cream to hot and spicy - only a few actually claim that their product is really nutritious or fortified with the necessary vitamins and minerals. A survey of the market shows, however, that customers do give importance to such characteristics as nutritive content. Hence, the proponents of this study ventured into the production of an alternative snack food which satisfies both the consumers' taste and their daily protein requirement. Rimostick, as the product is to be known, is a deep-fried snack food made from rice, mongo and sesame blend. It has been found to offer a protein value 8.4% higher than the maximum available in the market today. A market study of the project identified the target market to be that part of the population of the National Capital Region (NCR) belonging to the age group 5-49 and to income class B and C. To answer the demand coming from this target market, the company established a yearly production equal to that of its closest competitor which has a market share of 1.1% of the total NCR supply. The technical analysis of the project showed that it can produce this amount using four production lines at two batches per line with overtime. The site would be located in San Vicente, Nueva Ecija requiring a production area of 518.12 square meters for the first year. After which, an expansion to 706.22 square meters to house two additional production lines is needed. The total project cost was found to be P 19,226,143.99. Half of the amount was financed by the partners and the other half by debt financing from SSS at 16% interest per annum with three years to pay. The financial statements for the project showed positive results. In fact, income for the first year is P 2,048,673.90. The project was profitable as shown by the financial ratios which also revealed that the company is both liquid and solvent for its five-year operation. The computed IRR for the project was at 24.9% with a payback period of three years and two months. A listing of the cost and benefits in undertaking the project showed benefits to both the community in the chosen site and the municipality as well. With all the results that were obtained, it can be concluded from the study that there is a market for the project and that it is technically possible, financially feasible and socially profitable to all the entities which the project will affect.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management.
Keywords: Rice crackers industry; Snack food industry; Participatory monitoring and evaluation (Project management)